The Impact of Work and Family Responsibilities on the Academic Performance of Part-Time Postgraduate Students in Rawalpindi, Pakistan. - Jamil Akhter; Sajjad Ahmed; 3.Muhammad Yasir Hayat; 4.Shaiqa Kiran; 5.Dr. Muhammad Anwar Ul Haq (Dialogue Social Science Review (DSSR), 2025)
This qualitative research paper aimed at investigating the issues that part-time postgraduate students have in Rawalpindi, Pakistan, in balancing school academic commitments, work responsibilities and family commitments. Overall results of this research, based on in-depth interviews with male and female students who take evening postgraduate courses, reveal the effects of competing demands on academic achievement, affective well-being and situations of role negotiation. The results indicated that although both sexes had to face the problem of role conflict, women had much more pressure to face since gender expectations are culturally reinforced. Family support became an important issue that either empowered or limited the student to advance in education due to family culture regarding roles and responsibilities. Emotional burnout, managing time, and lack of institutional support to maintain performance were cited as some of the main barriers to success by many of the participants. The paper utilised the role conflict theory to explain how duplication of roles created both internal stress and external stress on the individuals, with implications on the schools and even policy makers, as well as parents. It suggests that the flexible academic policies, workplace accommodations, and culturally sensitive support systems are crucial to enhance the academic performance of students in the case of dual or triple roles. Keywords: Work-study balance, family responsibilities, part-time students, gender roles, academic performance, role conflict, higher education, Pakistan.